Standards For Media Education As A Basis For The Empirical Recording Of Media Literacy Levels - Tulodziecki, Gerhard (MediaEducation: Journal for Theory and Practice of Media Education, 2010)
Various international comparative studies on pupils' competences have made the demand for educational standards ever louder. In the course of corresponding developments, educational standards have been agreed upon for central subjects. Their formulation and review are considered an important instrument for quality assurance. It is therefore not surprising that in the meantime the demand for educational standards has also been raised for the field of media education and that first drafts are available (cf. e.g. Moser 2006; Tulodziecki 2007a, 2007b). However, media education occupies a special position in the educational policy discussion because it is not a subject but a cross-curricular area. For this reason in particular - also against the background of different conceptual approaches to media education - it should be kept in mind that media education enters a field of tension with the formulation of standards, which is characterised by different and partly diverging perspectives.